2018
DOI: 10.21037/tlcr.2018.09.23
|View full text |Cite
|
Sign up to set email alerts
|

Measuring tumor mutation burden in non-small cell lung cancer: tissue versus liquid biopsy

Abstract: The introduction in the clinic of immune checkpoint inhibitors (IOs) has represented an important improvement for the treatment of patients with advanced non-small cell lung cancer (NSCLC). These drugs have shown a higher activity as compared with chemotherapy in both first-and second-line of treatment, with some patients experiencing a long-lasting response. More recently, combinations of IOs have entered clinical trials in different tumor types including NSCLC. Nevertheless, IOs are active only in a subgroup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 47 publications
0
46
0
Order By: Relevance
“…In addition, the evaluation of tumor mutational burden (TMB), which is the number of somatic mutations in the genome coding regions (Mut/Mb), has been explored and is currently been tested in the cfDNA, to identify patients who can benefit from immunotherapy [99][100][101][102]. However, the first results on the concordance between tissue and cfDNA are contrasting [103]. One of the major issues is the lack of standardization in the TMB evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the evaluation of tumor mutational burden (TMB), which is the number of somatic mutations in the genome coding regions (Mut/Mb), has been explored and is currently been tested in the cfDNA, to identify patients who can benefit from immunotherapy [99][100][101][102]. However, the first results on the concordance between tissue and cfDNA are contrasting [103]. One of the major issues is the lack of standardization in the TMB evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…TMB has emerged as an independent biomarker to predict patient responses to treatment with ICIs, 18,19,49,50 and the negative predictive role of low TMB could not be overcome by the combination immunotherapy. 50 Several studies have shown to effectively measure TMB from liquid biopsies/blood, [51][52][53][54] this might be an alternative to the biopsies since it is less invasive and easily repeatable. However, TMB assessment by liquid biopsy must face the problem that the circulating DNA deriving from tumor cells is often only a small fraction of the circulating cell free DNA and it needs further investigation and may be clarified within the ongoing clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with circulating tumor DNA (ctDNA) testing, tissue testing is still the current mainstream method [36]. Blood testing has the advantage of convenient material collection, but the testing technology needs further investigation [37]. In this study, a total of three articles with four studies [26,38,39] used blood samples, and the results were heterogeneous so that no credible conclusions could be drawn about the validity of the blood test results.…”
Section: Discussionmentioning
confidence: 98%